Real-time source contribution analysis of ambient ozone using an enhanced meta-modeling approach over the Pearl River Delta Region of China. (15th August 2020) - Fang, Tingting; Zhu, Yun; Jang, Jicheng; Wang, Shuxiao; Xing, Jia; Chiang, Pen-Chi; Fan, Shaojia; You, Zhiqiang; Li, Jinying
Abstract: The nonlinear response of O3 to nitrogen oxides (NOx ) and volatile organic compounds (VOC) is not conducive to accurately identify the various source contributions and O3 -NOx -VOC relationships. An enhanced meta-modeling approach, polynomial functions based response surface modeling coupled with the sectoral linear fitting technique (pf-ERSM-SL), integrating a new differential method (DM), was proposed to break through the limitation. The pf-ERSM-SL with DM was applied for analysis of O3 formation regime and real-time source contributions in July and October 2015 over the Pearl River Delta Region (PRD) of Mainland China. According to evaluations, the pf-ERSM-SL with DM was proven to be effective in source apportionment when the traditional sensitivity analysis was unsuitable for deriving the source contributions in the nonlinear system. After diagnosing the O3 -NOx -VOC relationships, O3 formation in most regions of the PRD was identified as a distinctive NOx -limited regime in July; in October, the initial VOC-limited regime was found at small emission reductions (less than 22–44%), but it will transit to NOx -limited when further reductions were implemented. Investigation of the source contributions suggested that NOx emissions were the dominated contributor when turning-off the anthropogenic emissions, occupying 85.41–94.90% and 52.60–75.37% of the peak O3 responses in July and October respectively in the receptor regions of the PRD; NOx emissions from the on-road mobile source (NOx _ORM) in Guangzhou (GZ), Dongguan&Shenzhen (DG&SZ) and Zhongshan (ZS) were identified as the main contributors. Consequently, the reinforced control of NOx _ORM is highly recommended to lower the ambient O3 in the PRD effectively. Graphical abstract: Image 1 Highlights: An enhanced meta-modeling approach, pf-ERSM-SL with differential method (DM), was developed. DM can well quantify the nonlinear chemistry in the process of O3 formation. Pf-ERSM-SL with DM can identify the O3 formation regime and real-time source contributions. NOx emissions are the dominated contributor to O3 in the PRD when at 100% reduction. On-road mobile NOx emissions control is a priority for O3 mitigation.